Investment Policy Analysis on the Development of the Financial Technology (Fintech) Industry - Gracia, Amadea Elenora (IHSA Institute, 2026)
The rapid growth of the financial technology (fintech) industry has transformed the global financial landscape and created new opportunities for innovation, financial inclusion, and economic development. This study aims to analyze the effectiveness of investment policies in supporting the development of the fintech industry, particularly in the context of emerging economies. The research adopts a mixed-methods approach, combining qualitative and quantitative techniques through data collection methods such as interviews, surveys, and document analysis. Data are obtained from government reports, fintech companies, and investors to provide a comprehensive understanding of policy implementation and its impact. The findings indicate that investment policies, including tax incentives, regulatory frameworks, and funding support mechanisms, play a significant role in attracting investment inflows, fostering innovation, and expanding financial inclusion. However, the effectiveness of these policies is often constrained by regulatory uncertainty, bureaucratic inefficiencies, limited coordination among institutions, and technological readiness challenges. The study also finds that political stability, economic conditions, and public trust significantly influence policy outcomes. In conclusion, while current investment policies have contributed positively to fintech development, there is a need for continuous improvement to enhance their effectiveness. Strengthening regulatory clarity, improving investor protection, encouraging innovation through targeted incentives, and fostering collaboration between stakeholders are essential to creating a more conducive fintech ecosystem. This research provides important insights for policymakers and industry practitioners in developing sustainable strategies to support fintech growth and maximize its contribution to economic development.